Gender dynamics in the performance of grade 7 certificate of primary education examinations in Gweru Urban District, Zimbabwe - Matope, Nogget; Chauraya, Efiritha; Maruzani, Nyevero (Global Institute for Research and Education, 2016)
The Education for All Act in Zimbabwe has endeavored to provide education to all irrespective of gender. The performance of the girl child has been unsatisfactory nationally. The study investigated gender – based factors which impact on performance in these school leaving examinations. The survey design was employed and 20 randomly selected schools in Gweru Urban Education District were used for the study. Purposive sampling was used to select 240 (120 girls and 120 boys) pupils from grade 7, 20 teachers and 20 school heads. Questionnaires and interviews were used to collect data from the school heads, teachers and pupils. The data gathered was organised and presented in the form of frequency schedules, counts and percentages where descriptive and inferential statistics were used for analysis. The findings revealed a significant difference in performance between boys and girls in examinations. School, community, individual and school factors affect girls more than boys. The study recommends the need for society to change bias towards female education. The stakeholders must ensure that girls are protected from retrogressive practices that impede their performance in examinations.